Green synthesis, characterization, and biological activities of saffron leaf extract‐mediated zinc oxide nanoparticles: A sustainable approach to reuse an agricultural waste. (16th May 2020) - Rahaiee, Somayeh; Ranjbar, Mojtaba; Azizi, Hossein; Govahi, Mostafa; Zare, Mahboobeh
Abstract : To increase the profitability and sustainability of agricultural waste, a facile green approach was established to synthesize zinc oxide nanoparticles (ZnO NPs) using saffron leaf extract as a reducing and stabilizing agent. Structural characteristics of NPs were investigated by X‐ray diffraction (XRD), Fourier‐transform infrared (FTIR), field emission scanning electron microscopy (FESEM), and UV–Visible (UV–Vis) spectroscopy. Characterization results revealed that ZnO NPs is highly crystalline with a hexagonal wurtzite structure and spherical particles with diameter less than 50 nm, as confirmed by XRD and FESEM techniques. UV–Vis absorption spectra depicted an absorption peak at 370 nm, which confirms the formation of ZnO NPs. FTIR spectral analysis confirmed the presence of functional groups and metal oxygen groups. The biological activities of ZnO NPs were also investigated. The antibacterial effect of ZnO NPs was investigated against selected food pathogens ( Salmonella Typhimurium, Listeria monocytogenes, and Enterococcus faecalis ). The study results prove that the green synthesized ZnO NPs show enhanced antibacterial activity against S. Typhimurium when compared with other strains. A dose‐dependent free radical scavenging activity was observed for ZnO NPs in both 2, 2‐diphenyl‐1‐picryl‐hydrazyl‐hydrate (DPPH) and fluorescence recovery after photobleaching (FRAP) assays. The ZnO NPs were evaluated for their photocatalytic activity during the degradation of methylene blue (MB) dye in aqueous solutions. The maximum removal of MB achieved was 64% with an initial ZnO NP concentration of 12 mg/mL under UV light. The present study revealed that the agricultural waste (saffron leaf) provides a simple and eco‐friendly option to sustainably synthesize ZnO NPs for use as a photocatalyst. In addition, this is the first report on saffron leaf‐mediated synthesis of ZnO NPs. Abstract : ZnO NPs were synthesized using the aqueous extract of Crocus sativus leaves and were characterized by various spectroscopic studies. The spherical‐shaped ZnO NPs showed excellent antibacterial and antioxidant activities in concentration‐dependent manner. ZnO NPs catalyst were degraded MB dye under UV light irradiation.